The Strategic Obstacles Preventing Israel's Attack on Iran's Nuclear Reactors - Jihad Aldeen Albadawi (European Scientific Journal, ESJ, 2021)
The study analyzes the reasons that prevent "Israel" from launching a comprehensive military strike against the nuclear sites and other vital sites of a military nature in Iran, in light of the escalation of the indirect military confrontation between them in many conflicts in the Middle East. The study summarizes the "Israeli" risks to implementing "preventive war" on the Iranian scene in four obstacles, which are: the operational, the legal, the military, and the armed non-state actors. The study concluded that: despite the blockade imposed on Iran, especially with regard to the import of advanced military equipment, Iran was able to build a relative deterrent force consisting of three pillars, which rest on its ability to (1) threaten navigation through the Strait of Hormuz, (2) undertake terrorist attacks on multiple continents, and (3) conduct long-range strikes, primarily by missiles (or with rockets owned by proxies deployed in many countries of the Middle East, and its ability to target "Israel" with short and medium-range ballistic missiles. The Iranian deterrent force, or what has come to be called the Iran’s deterrence triad, was the real obstacle to Israel from launching a preventive war against Iran.